Erasing the past, redesigning the nation: toponymic change, heritage signage, and contested memory in Indonesian public space - Eka Fitri Hastuti (Indonesian Journal of Language, Space, and Visual Arts, 2026)
Background: Public space has increasingly become a strategic arena where historical narratives, cultural identities, and political authority are negotiated through spatial symbols, commemorative practices, and heritage representation. Objective: This study investigates how toponymic change and heritage signage participate in the production, reinterpretation, and contestation of collective memory within Indonesian public space. Method: This study employs a qualitative corpus-based design integrating critical toponymy, multimodal heritage signage analysis, and memory politics, drawing on official naming documents, heritage signage materials, visual identity artefacts, policy texts, and contextual reports. Results: Findings indicate that commemorative renaming primarily functions as a mechanism for re-inscribing nationally preferred historical narratives into everyday spatial environments. Heritage signage further reinforces these narratives through multimodal combinations of language, visual symbolism, institutional branding, and spatial design that shape public interpretation of the past. Implication: At the same time, memory is not simply preserved or erased; rather, public space emerges as a site where historical meanings are selectively amplified, reinterpreted, and negotiated across competing scales of identity and heritage. Novelty: The novelty of this study lies in integrating critical toponymy, multimodal heritage signage, and memory politics into a unified analytical framework that explains how spatial naming and visual heritage infrastructures jointly contribute to the redesign of national historical consciousness.